Psychological content parameters of attention in the structure of time perspective of young female athletes: comparative analysis - Popovych, Ihor; Hulias, Inesa; Serbin, Iyuriy; Piletska, Liybomyra; Mashcak, Svitlana; Zahrai, Larysa (My University, 2023)
The purpose of the research is to determine dependence of the parameters of attention on the dominating time perspective and compare significant differences in the representatives of individual and team sports. The research participants are female athletes of sports schools for children and youth. The sample of individual sports (Group 1) included representatives of rhythmic gymnastics and track and field (n = 35; 52.24%). The sample of team sports (Group 2) involved of handball players and volleyball players (n = 32; 47.76%). Research methods applied: “Schulte Tables” (Rogov, 1999), “Landolt C Rings”, (Pashukova et al., 1996); “Munsterberg Test” (Pashukova et al., 1996); “Zimbardo Time Perspective Inventory” (Zimbardo & Gonzalez, 1984). Results. A graphical structure of young female athletes’ time perspective was created. No significant differences between the parameters of attention between the athletes in individual (Group 1) and team sports (Group 2) were found. The research substantiates that the formation of the parameters of attention in youth does not depend on a kind of sport. Correlations between the parameters of attention and the parameters of time perspective were determined (р<.05; р<.01). It was established that the future (F) has most significant correlations – four – with the main parameters of attention: stability (.095; p≤.05), concentration (.107; p≤.05), volume (.212; p≤.01) and selectivity (.094; p≤.05). It was emphasized that domination of orientation towards the future in the dimensions of attention is a factor of successful educational and training activities of young female athletes. There were differences between the groups of athletes with different parameters of attention determined by the median (Me). It was proved that the formation of high levels of attention ensures achievement of the results of educational and training activities of young female athletes and focuses their activity in the dimensions of time orientations: the future (F), the hedonistic present (HP), the positive past (PP). Conclusions. The obtained empirical facts should be operationalized into educational and training activities at sports schools for children and youth.
Keywords: concentration of attention; stability of attention; volume of attention; selectivity of attention; cognitive processes; self-regulation